2020
DOI: 10.3390/vision4010019
|View full text |Cite
|
Sign up to set email alerts
|

The Dominant Eye: Dominant for Parvo- But Not for Magno-Biased Stimuli?

Abstract: Eye dominance is often defined as a preference for the visual input of one eye to the other. Implicit in this definition is the dominant eye has better visual function. Several studies have investigated the effect of visual direction or defocus on ocular dominance, but there is less evidence connecting ocular dominance and monocular visual thresholds. We used the classic “hole in card” method to determine the dominant eye for 28 adult observers (11 males and 17 females). We then compared contrast thresholds be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 43 publications
(51 reference statements)
1
3
0
Order By: Relevance
“…The current study findings suggest that visual disturbances caused by stroboscopic light during exercise indicate that perceptual processing priority is a function of the dominant eye. This finding aligns with prior research that demonstrated the superior performance of the dominant eye during binocular viewing conditions ( Foutch and Bassi, 2020 ; Handa et al, 2004 ; Hofeldt et al, 1996 ). In future research, it would be valuable to design an experiment examining the effects of a stroboscopic intervention that primarily stimulates the non-dominant eye.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The current study findings suggest that visual disturbances caused by stroboscopic light during exercise indicate that perceptual processing priority is a function of the dominant eye. This finding aligns with prior research that demonstrated the superior performance of the dominant eye during binocular viewing conditions ( Foutch and Bassi, 2020 ; Handa et al, 2004 ; Hofeldt et al, 1996 ). In future research, it would be valuable to design an experiment examining the effects of a stroboscopic intervention that primarily stimulates the non-dominant eye.…”
Section: Discussionsupporting
confidence: 91%
“…The training intervention included stimulation of both pathways, with a large effect on extra-foveal vision and the dominant eye. It is thought that parvocellular-biased objects seen through the dominant eye are somehow more discernible than those seen by the non-dominant eye ( Foutch and Bassi, 2020 ), which may partially explain the findings observed in the study. The chessboard pattern stimulation and achromatic high-contrast stimulation ISCEV VEPs used in this study mainly concern the parvocellular pathway ( Benedek et al, 2016 ).…”
Section: Discussionmentioning
confidence: 59%
“…Witkowski et al studied the cognitive steps taken by customers when they booked a room online and the effects of website aesthetics on their booking intention [ 9 ]. Foutch and Bassi proved the relationship between the dominant eye and monocular vision threshold [ 10 ]. These results demonstrate that physiological characteristics have a certain degree of influence on the human body’s abilities and cognition.…”
Section: Introductionmentioning
confidence: 99%
“…Most research on physiological characteristics is in the fields of physiology, medicine, or sports [5][6][7][8][9][10]. Mohr found that right-handed people prefer to turn left, and left-handed people prefer to turn right.…”
Section: Introductionmentioning
confidence: 99%